Detachment evolution on the TCV tokamak. (August 2017) - Harrison, J.R.; Vijvers, W.A.J.; Theiler, C.; Duval, B.P.; Elmore, S.; Labit, B.; Lipschultz, B.; van Limpt, S.H.M.; Lisgo, S.W.; Tsui, C.K.; Reimerdes, H.; Sheikh, U.; et al.
Highlights: A detailed analysis of data from several diagnostics on TCV has been carried out to study divertor detachment in dedicated experiments. The detachment "front" location has been tracked during the evolution of detachment inferred from tomographically inverted C III and Dα emission. The analysed data was found to have good overall consistency, which has been verified using OSM-EIRENE-DIVIMP modelling. Abstract: Divertor detachment in the TCV tokamak has been investigated through experiments and modelling. Density ramp experiments were carried out in ohmic heated L-mode pulses with the ion ∇B drift directed away from the primary X-point, similar to previous studies[1] . Before the roll-over in the ion current to the outer strike point, C III and Dα emission from the outer leg recede slowly from the strike point toward the X-point, at a rate of ∼2.0 × 10 −19 m/m −3 along the magnetic field as the electron temperature along the leg reduces with increasing density. Around the onset of detachment, the upstream density profile and outer target Dα profiles broaden, possibly leading to an increase in radiation in the SOL by increased interaction between the SOL and the carbon tiles lining the outer wall. The plasma conditions upstream and at various locations along the detached outer divertor leg have been characterised, and the consistency of this data has been checked with the interpretive OSM-EIRENE-DIVIMP suite of codes[2] and are broadly found to be consistent with measured Dγ /Dα emissivity profiles along the detached outer divertor leg.